LC Evaluation of In Vitro Release of AZT from Microemulsions - Carvalho, Flavia Chiva [UNESP]; Barbi, Mariana da Silva [UNESP]; Gremião, Maria Palmira Daflon [UNESP] (Vieweg, 2009)
A reversed phase LC method was developed and validated to analyze the in vitro release of AZT from microemulsions. A mobile phase of acetonitrile:water (15:85) was used. The method validation showed good selectivity and linearity (r = 0.9993) for sample concentrations ranging from 0.6 to 100.0 mu g mL(-1). The RSD values (0.7-4.3%) and percentage recovery (88.1-109.8%) were within acceptable limits. The limit of detection (LOD) and limit of quantitation (LOQ) were found to be 0.012 and 0.041 mu g mL(-1). Quantitative analysis of the values obtained in the drug release assay indicates that the microemulsions used promote sustained release of AZT, which follows a Fickian diffusion mechanism.
Keywords: Column liquid chromatography; In vitro drug release; Drug delivery system; Zidovudine